Outcomes at 7 years post‐transplant in black vs nonblack kidney transplant recipients administered belatacept or cyclosporine in BENEFIT and BENEFIT‐EXT. Issue 4 (14th March 2018) - Florman, Sander; Vincenti, Flavio; Durrbach, Antoine; Abouljoud, Marwan; Bresnahan, Barbara; Garcia, Valter Duro; Mulloy, Laura; Rice, Kim; Rostaing, Lionel; Zayas, Carlos; Calderon, Kellie; Meier‐Kriesche, Ulf; et al.
Abstract: Clinical outcomes are generally worse for black vs nonblack renal allograft recipients. In BENEFIT and BENEFIT‐EXT, recipients were randomized to belatacept more intense‐based, belatacept less intense‐based, or cyclosporine‐based immunosuppression. At year 7, belatacept was associated with superior graft survival vs cyclosporine in BENEFIT (recipients of living or standard criteria deceased donor kidneys); belatacept was associated with similar graft survival vs cyclosporine in BENEFIT‐EXT (recipients of extended criteria donor kidneys). In both studies, renal function was superior for belatacept‐treated vs cyclosporine‐treated patients. Seven‐year outcomes were examined by race post hoc in each study. The effect of race and treatment on time to death or graft loss was compared using Cox regression. The interaction between treatment and race was also considered. Glomerular filtration rate (GFR) was estimated from months 1 to 84 using a repeated‐measures model. In total, 8.3% (55/666) and 13.1% (71/543) of patients in BENEFIT and BENEFIT‐EXT, respectively, were black. Time to death or graft loss was similar in blacks and nonblacks. For both subgroups, estimated mean GFR increased over 7 years for belatacept, but declined for cyclosporine. Outcomes were similar in belatacept‐treated black and nonblack patients. Due to the small number of black patients, these results must be interpreted with caution.